Be your own CBT therapist - Dryden, Windy (London Teach Yourself, 2011)
Dryden shows you how to beat the thought patterns that lead to low mood and help you to develop a more balanced attitude, with a resilient, focused approach toward life's obstacles. -- Provided by the publisher.
What is Rational Emotive Behaviour Therapy (REBT)?: an introduction -- Understanding the "situational ABC" framework -- Tackling your problems: an overview -- Identifying and formulating your problems and goals -- Selecting and working with a target problem and a specific example of that problem -- Using the "situational ABC" framework to access your specific example and to set goals -- Focusing on and questioning your beliefs -- Strengthening your conviction in your rational beliefs -- Responding to highly distorted thoughts at "C" -- Coming back to "A" -- Using established and new skills across the board -- Dealing with lapses and preventing relapse -- Maintaining your gains -- Dealing with obstacles to change -- Dealing with anxiety -- Dealing with depression.
Keywords: Cognitive Behavioral; Therapy Cognitive therapy